The Composition of The Catch of Mini Purse Seine in The Java Sea - Muhammad Iqbal Mubarok; Beta Indy Sulistyowati; Robet Perangin-angin; Eli Nurlaela (Yayasan Serumpun Karang Konservasi, 2023)
Pelagic fish are a type of fish that live in groups, with their habitat in shallow waters or sea level. Groups of small pelagic fish living in coastal waters and juveniles (kids) are known to be more abundant on the north coast of Java, which is a traditional mini purse seine fishing area. This study aims to analyze the catch composition of the mini purse seine fishing unit, which is operated in the Java Sea. The composition of the catch obtained using the mini purse seine fishing gear operating in the northern part of the Java Sea is dominated by small pelagic fish, which are the main catches mackerel (Rastrelliger sp.) 76%, white sardinella (Sardinella sp.) 18 %, and Splendid ponyfish (Eubleekeria splendens) by 4%, as for the bycatch obtained in the form of Largehead hairtail (Trichiurus lepturus), squid (Loligo sp.), Kawakawa (Euthynnus affinis), and other fish.